MULTILATERALISME TIONGKOK: TINJAUAN FAKTOR DOMESTIK YANG MEMPENGARUHI PENDIRIAN AIIB - Emilia Kurniasari; Asra Virgianita; Ardhitya Eduard Yeremia (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2022)
This article seeks to explore how China understands multilateralism. Employing content analysis, this article analyzes Chinese leaders’ speeches surrounding the establishment of AIIB. The result finds that within the speeches, “fazhan” (development/to develop) is the most frequently mentioned word. The narratives concerning the word suggest that from the China perspective, a multilateral cooperation framework is instrumental to pursue its long-term geopolitical goals. For China, multilateral practices should be based on the principle of flexibility. On the one hand, the implementation of such a principle is central in projecting the image of China as being accommodative. On the other hand, it is fundamentally instrumental to ensure that China would have wider room to maneuver in achieving and defending its interests. Keywords: Asian Infrastructure Investment Bank, China, economic development, global governance, multilateralism